Recognition of Variants of Concern by Antibodies and T Cells Induced by a SARS-CoV-2 Inactivated Vaccine - Melo-González, Felipe; Soto, Jorge A.; González, Liliana A.; Fernández, Jorge; Duarte, Luisa F.; Schultz, Bárbara M.; Gálvez, Nicolás M. S.; Pacheco, Gaspar A.; Ríos, Mariana; Vázquez, Yaneisi; Rivera-Pérez, Daniela; Moreno-Tapia, Daniela; et al. (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus responsible of the current pandemic ongoing all around the world. Since its discovery in 2019, several circulating variants have emerged and some of them are associated with increased infections and death rate. Despite the genetic differences among these variants, vaccines approved for human use have shown a good immunogenic and protective response against them. In Chile, over 70% of the vaccinated population is immunized with CoronaVac, an inactivated SARS-CoV-2 vaccine. The immune response elicited by this vaccine has been described against the first SARS-CoV-2 strain isolated from Wuhan, China, and the D614G strain. Here, we describe the neutralizing capacities of antibodies secreted by volunteers in the Chilean population immunized with CoronaVac against variants of concern Alpha (B.1.1.7), Beta (B.1.351) Gamma (P.1), and Delta (B.617.2). Volunteers enrolled in the phase 3 clinical trial were vaccinated with two doses of CoronaVac in 0-14 or 0-28 immunization schedules. Sera samples were used to evaluate the neutralizing capacity antibodies against variants of concern by an in-house ELISA and conventional microneutralization assays. Moreover, interferon--secreting T cells against Spike variants of concern were evaluated using ELISPOT. CoronaVac promotes the secretion of antibodies able to block the RBD of all the SARS-CoV-2 variants studied. Seropositivity rates of neutralizing antibodies were over 97% for the wild-type strain, over 80% for Alpha and Gamma variants, over 75% for the Delta variant, and over 60% for the Beta variant. Geometric means titers of blocking antibodies were reduced against the SARS-CoV-2 variants as compared to ancestral strain. Also, antibodies from vaccinated subjects neutralize the infection of variants D614G, Alpha, Gamma, and Delta in a conventional microneutralization assay. Importantly, after SARS-CoV-2 infection, the blocking capacity of antibodies from vaccinated volunteers increased for all the variants tested. The number of interferon-y-secreting T cells specific for SARS-CoV-2 Spike WT and variants of concern from vaccinated subjects was not significantly different. Immunization with CoronaVac in either immunization schedule promotes the secretion of antibodies able to block SARS-CoV-2 variants of concern and partially neutralizes SARS-CoV-2 infection. Further, it stimulates cellular responses against all variants of concern.